Seismic performance of reinforced concrete columns with plain longitudinal reinforcing bars - Pham, Thanh Phuong (2014)
This paper presents an experimental investigation carried out on nine reinforced concrete (RC) columns with plain longitudinal reinforcing bars subjected to simulated seismic loadings. The variables of interest are axial loads, aspect ratios, and cross sectional shapes. The performance of specimens was discussed in terms of crack patterns, hysteretic response, initial stiffness, shear strength, drift capacity, and energy dissipation capacity. The test results were compared with available experimental data of five RC columns reinforced with deformed reinforcing bars. The comparisons highlighted that apart from lower shear capacities; columns with plain longitudinal bars have rather large initial stiffness and drift capacities, even higher than columns with deformed longitudinal reinforcing bars. Further comparisons with the existing model for evaluation of existing structures revealed that the ASCE/SEI 41-06 provision tends to overestimate initial stiffness and shear strength, but substantially underestimates drift capacities of columns with plain reinforcing bars. A correction factor is therefore proposed when employing ASCE/SEI 41-06 concrete provisions for shear strength evaluation of RC columns with plain longitudinal reinforcement.